2020
DOI: 10.3390/ijms21020454
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Rice Expansin7 (Osexpa7) Confers Enhanced Tolerance to Salt Stress in Rice

Abstract: Expansins are key regulators of cell-wall extension and are also involved in the abiotic stress response. In this study, we evaluated the function of OsEXPA7 involved in salt stress tolerance. Phenotypic analysis showed that OsEXPA7 overexpression remarkably enhanced tolerance to salt stress. OsEXPA7 was highly expressed in the shoot apical meristem, root, and the leaf sheath. Promoter activity of OsEXPA7:GUS was mainly observed in vascular tissues of roots and leaves. Morphological analysis revealed structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 109 publications
2
51
0
Order By: Relevance
“…Thus, the overaccumulation of expansins under salt stress would not favor cell wall expansion but rather participate to the salt stress signaling pathway. Several studies showed that overexpression of an expansin gene in Arabidopsis was shown to confer enhanced salt tolerance by lowering ROS accumulation and increasing antioxidant activity ( Abuqamar et al, 2013 ; Lü et al, 2013 ; Chen et al, 2019 ; Jadamba et al, 2020 ). Thus, the higher abundance of FLAs associated with a higher overaccumulation of expansins observed in Ws could contribute to a better CWI in response to salt stress than Col-0, where only one FLA and WAK1 were overaccumulated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the overaccumulation of expansins under salt stress would not favor cell wall expansion but rather participate to the salt stress signaling pathway. Several studies showed that overexpression of an expansin gene in Arabidopsis was shown to confer enhanced salt tolerance by lowering ROS accumulation and increasing antioxidant activity ( Abuqamar et al, 2013 ; Lü et al, 2013 ; Chen et al, 2019 ; Jadamba et al, 2020 ). Thus, the higher abundance of FLAs associated with a higher overaccumulation of expansins observed in Ws could contribute to a better CWI in response to salt stress than Col-0, where only one FLA and WAK1 were overaccumulated.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of ZmEXPB6 is correlated with the reduced leaf growth of maize under salt stress [ 89 ]. Overexpression of rice expansin 7 ( OsEXPA7 ) confers substantially enhanced tolerance to salt stress by lowering reactive oxygen species (ROS) accumulation and increasing antioxidant activity in rice [ 90 ]. Ectopic expression of wheat expansin 2 ( TaEXPA2 ) or TaEXPB23 improves salt tolerance in tobacco [ 91 , 92 ].…”
Section: The Roles Of the Cell Wall-localized Glycoproteins In Salmentioning
confidence: 99%
“…Thirty-six and 38 genes were homologous to arabidopsis and rice, respectively (Supplementary Table 7). Six predicted genes, included AET2Gv20774800, AET4Gv20799000, AET5Gv20005900, AET5Gv20084100, AET7Gv20644900, and AET5Gv21111700, were homologous to MST1 (Takeda et al, 2001;Mao et al, 2011), MAC3B (Monaghan et al, 2009;Li S. et al, 2018), ETR1 (Yin et al, 2017), ZAR1 (Guo et al, 2013;Yu et al, 2016), NAC047 (Kunieda et al, 2008;Mathew et al, 2016), EXPA7 (Lizana et al, 2010;Jadamba et al, 2020), respectively (Table 5). These genes (MST1, MAC3B, ETR1, ZAR1, NAC047, EXPA7) could affect embryo development, cause seed surface atrophy, increase the number of cells to increase organ size, or affect kernel size through ethylene response.…”
Section: Candidate Genes That May Be Linked To Kernel Traitsmentioning
confidence: 99%